Preoperative Fasting and Blood Sugar Highlights Emergency Complications in General Anesthesia Patients - Yenni Elfira; Irwadi Irwadi; Fatimah Fatimah (Indonesian Journal of Global Health Research, 2025)
Fasting that is too long will affect the patient's condition, one of which is the patient's blood sugar levels. In this case, it is necessary to control the start time of fasting with the time of the operation that the patient will undergo. The purpose of the study was to determine Preoperative Fasting and Blood Sugar Highlighting Emergency Complications in General Anesthesia Patients at Dr. Reksodiwiryo Class III Hospital in Padang. A correlational analytical observational study was conducted using a cross-sectional approach. This observational analytical correlational study was conducted with a cross-sectional approach. The number of samples was 34 people, the sampling technique used consecutive sampling. This research instrument used an observation sheet and a blood sugar level monitoring tool (Glucometer) With the respondent criteria determined according to the inclusion and exclusion criteria. The test results showed that there was a relationship between the length of fasting and blood sugar levels highlighting emergencies in preoperative general anesthesia patients at Dr. Reksodiwiryo Class III Hospital in Padang with a p value = 0.005. It can be concluded that the duration of preoperative fasting can affect blood sugar levels in general anesthesia patients which causes patients to become hypoglycemic or hyperglycemic which triggers various emergency complications that can worsen the patient's clinical condition when undergoing general anesthesia.